Harmonization of color measurements for dental application - Paravina, Rade D.; Pereira Sanchez, Natalie A.; Tango, Rubens N. [UNESP] (Wiley-Blackwell, 2020)
This multicenter study evaluated the effect of harmonizing spectrophotometric (d/8 degrees) color measurements by using actual dental materials of clinically relevant thickness and translucency as calibration tiles. Ten tooth-colored, 1-mm thick, resin- and ceramic-based materials were tested at the coordinating center (CC) and six research sites (RS). Correction factors were calculated for each material and each site to obtain the corrected reflection spectra from the non-corrected data set. Non-corrected ((NC)) and corrected ((C)) reflection values were converted into CIEDE2000 and CIELAB color parameters for the following comparisons: CC vs RSNC and CC vs RSC, between RSNC vs RSNC and RSC vs RSC pairs, and among RS separately (alpha = 0.05). Mean color differences for CC vs RSNC and corresponding CC vs RSC values were Delta E-00 = 4.2 (2.6) and Delta E-00 = 0.7 (0.6), respectively. Corresponding values for RSNC vs RSNC and RSC vs RSC specimen pairs were Delta E-00 = 5.9 (2.9) and Delta E-00 = 1.0 (0.5), respectively. The CIEDE2000 NC vs C comparison for each research site separately ranged from 0.5 to 8.5. Color differences of CC vs RSC and RSC vs RSC pairs decreased 83% to 84.5% as compared with respective color differences for non-corrected research site measurements and was RS dependent (P <.001). The obtained results validated the proposed method of harmonizing color measurements for dental application as a reliable quality control tool for dental research laboratories and industry.
Keywords: color harmonization; color tolerances; dentistry; aesthetics; psychophysics; spectrophotometry